Menyoal Konsep Demokrasi Amerika Serikat: Promosi dan Trajektorinya - Arifianto, Muhamad Lukman (Jurnal Keamanan Nasional, 2017)
AbstractPost World War II and after Cold War period, international community realized the importance to create a peaceful system without war. United State as the winner of those wars has been accounted to have ability in promoting democracy and global peace that prioritized offensive liberal approach by optimizing the use of military approach pushed by his fear of his hegemony position. In the same spectrum, the national interest of democracy states are certainly more hurdle in getting benefit from being a democracy state. Even though globalization effect has opened wide opportunity for individual in democracy state to make a cooperation – military, economy, and investment on social-culture with non-democracy state, such as China, the share of benefit in geo-political between promoter of democracy and democracy imported state are things to be anticipated by democracy state. It is importance to review the process and relation character between the imported democracy states with US, which in general begin through mechanism and varieties of bandwagoning.